2023
DOI: 10.1002/adma.202300731
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Opportunities of Eco‐Friendly Ternary Copper Halides: A New Superstar in Optoelectronic Applications

Abstract: Recently, the newly‐emerging lead‐free metal‐halide materials with less toxicity and superior optoelectronic properties have received wide attention as the safer and potentially more robust alternatives to lead‐based perovskite counterparts. Among them, ternary copper halides (TCHs) have become a vital group due to their unique features, including abundant structural diversity, ease of synthesis, unprecedented optoelectronic properties, high abundance, and low cost. Although the recent efforts in this field ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 247 publications
(633 reference statements)
1
24
0
Order By: Relevance
“…These studies have demonstrated the crucial role that this compound's distinctive structural and electronic characteristics play. [21][22][23][24][25][26] Notably, the perovskite structure exhibits a remarkable degree of symmetry, which contributes significantly to its photovoltaic applications. Furthermore, the defect-tolerant nature of CH 3 NH 3 PbI 3 further enhances its photovoltaic performance.…”
mentioning
confidence: 99%
“…These studies have demonstrated the crucial role that this compound's distinctive structural and electronic characteristics play. [21][22][23][24][25][26] Notably, the perovskite structure exhibits a remarkable degree of symmetry, which contributes significantly to its photovoltaic applications. Furthermore, the defect-tolerant nature of CH 3 NH 3 PbI 3 further enhances its photovoltaic performance.…”
mentioning
confidence: 99%
“…Recently, low-dimensional metal halides have generated significant research interest in many optoelectronic applications due to their desirable photophysical properties. Among these, copper metal halides have emerged as a vital group due to their nontoxic nature and excellent optoelectronic properties, including simple synthesis and processing methods. Cu­(I)-based metal halides have been investigated in photodetectors, X-ray scintillators, image sensors, temperature sensors, memristors and neuromorphic computing, fluorescent inks, anticounterfeiting, and encryption applications. , Cu exhibits multiple coordination numbers, which can form 2D layers, 1D chains, and isolated 0D units . Additionally, the Cu­(I) metal halides have a wide range of structural tunability; depending on the composition of ACuX (A: Cs, Rb, K, and X: Cl, Br, I), they form different crystal phases. Each structure exhibits distinctive physical, chemical, and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are significant in the field of optoelectronics, thereby rendering 0D lead-free metal halide perovskites the most promising next generation lighting materials. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Cs 3 Cu 2 Cl 5 is widely used in photoelectric applications, including light-emitting devices (LEDs), [24] X-ray detection, [25] sensors, [26] high-resolution X-ray imaging, [27,28] and light communications. [29] Despite being a novel photoelectric material, Cs 3 Cu 2 Cl 5 has received limited attention compared with Cs 3 Cu 2 I 5 , because of the challenges in 1) obtaining large bulk single crystals and 2) its instability in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%